The Mitochondria-Regulated Immune Pathway Activated in the C. elegans Intestine Is Neuroprotective - Chikka, Madhusudana Rao; Anbalagan, Charumathi; Dvorak, Katherine; Dombeck, Kyle; Prahlad, Veena (Cell reports (Cambridge), 2016)
Immunological mediators that originate outside the nervous system can affect neuronal health. However, their roles in neurodegeneration remain largely unknown. Here, we show that the p38MAPK-mediated immune pathway activated in intestinal cells of Caenorhabditis elegans upon mitochondrial dysfunction protects neurons in a cell-non-autonomous fashion. Specifically, mitochondrial complex I dysfunction induced by rotenone activates the p38MAPK/CREB/ATF-7-dependent innate immune response pathway in intestinal cells of C. elegans. Activation of p38MAPK in the gut is neuroprotective. Enhancing the p38MAPK-mediated immune pathway in intestinal cells alone suppresses rotenone-induced dopaminergic neuron loss, while downregulating it in the intestine exacerbates neurodegeneration. The p38MAPK/ATF-7 immune pathway modulates autophagy and requires autophagy and the PTEN-induced putative kinase PINK-1 for conferring neuroprotection. Thus, mitochondrial damage induces the clearance of mitochondria by the immune pathway, protecting the organism from the toxic effects of mitochondrial dysfunction. We propose that mitochondria are subject to constant surveillance by innate immune mechanisms. [Display omitted] •Rotenone exposure activates the p38MAPK/ATF-7 immune pathway in the C. elegans gut•The p38MAPK/ATF-7 immune pathway is triggered by mitochondrial complex I dysfunction•p38MAPK/ATF-7 activity in the gut protects from rotenone-induced neurodegeneration•Neuroprotection through p38MAPK/ATF-7 activation occurs through mitophagy Chikka et al. find that mitochondrial complex I damage activates the p38MAPK/ATF-7 signaling pathway in the intestine of C. elegans. Activation of the p38MAPK/ATF-7 immune pathway in the intestine is neuroprotective and sufficient to prevent rotenone-induced degeneration of dopaminergic neurons.